200 Evaluating Performance of Calf-Fed Steers Fed Steam-Flaked Corn Based Finishing Diets with Varying Levels of Distillers Grains. (12th April 2022) - Troyer, Braden; Norman, Mitch; McPhillips, Levi J; Watson, Andrea K; MacDonald, Jim C; Erickson, Galen E
Abstract: Steam-flaked corn (SFC) is becoming more common in Northern Plains and Midwest feeding areas. While performance benefits of feeding wet (WDGS) or modified (MDGS) distillers grains are well documented in diets with dry-rolled or high-moisture corn, fewer data are available evaluating distillers grains in SFC-based diets. Therefore, the objective of this study was to evaluate performance when feeding WDGS or MDGS at increasing inclusions in SFC-based finishing diets. Crossbred steers (n = 560; initial BW = 299 kg; SD = 15 kg) were utilized in a 2 × 3 + 1 factorial design with factors consisting of 2 distillers types (MDGS or WDGS) fed at 1 of 3 inclusions (10%, 20%, or 30%) replacing SFC on a dry matter (DM) basis. A 0% distillers treatment was used for determining type by inclusion interactions. An interaction between type and inclusion of distillers was observed for dry matter intake (DMI; P = 0.06) and feed efficiency (G:F; P =0.02). Intake for steers fed WDGS tended to quadratically increase ( P = 0.08), while steers fed MDGS had a more dramatic linear increase ( P < 0.01) in DMI. Increasing WDGS inclusion resulted in a linear increase in G:F (P = 0.01), whereas increasing MDGS inclusion had no effect on G:F ( P = 0.16). No interaction between type and inclusion of distillers grains for other variables ( P > 0.20). Feeding distillers grains, regardless of type, resulted in linear increases in daily gain (ADG), hot carcass weight, and backfat ( P ≤ 0.03). Control cattle gained 1.73 kg/d while cattle fed 30% MDGS and WDGS had ADG of 1.88 kg/d and 1.90 kg/d, respectively. Overall, gain of calf-fed steers was improved when distillers grains was increased in steam-flaked corn based finishing diets regardless of type, but G:F was increased with WDGS and not MDGS suggesting feeding WDGS provides more energy than MDGS in SFC-based diets.